Draft Annual Plan 1986-87 Volume : X Hill Areas Government of Assam - Planning Commission (Planning Commission, 1986)
The total allocation for the Sixth Five Year Plan (1980-85). for General Education (Hills Areas) is Rs. 616.10 lakhs under state Plan against the tentative outlay of Rs. 500.00 lakhs and Rs. 340.72 lakhs under Additive Plan against the tentative outlay of Rs. 100.00 lakhs.
Government of Assam